CC–LR: providing interactive, challenging and attractive Collaborative Complex Learning Resources. (13th June 2013) - Caballé, S.; Mora, N.; Feidakis, M.; Gañán, D.; Conesa, J.; Daradoumis, T.; Prieto, J.
Abstract Many researchers argue that students must be meaningfully engaged in the learning resources for effective learning to occur. However, current online learners still report a problematic lack of attractive and challenging learning resources that engage them in the learning process. This endemic problem is even more evident in online collaborative learning approaches whose resources lack of authentic interactivity, user empowerment, social identity and challenge, thus having a negative effect on learners' self‐motivation and engagement. To overcome these and other limitations and deficiencies, in this paper, a new type of learning resource named Collaborative Complex Learning Resources (CC–LR) is presented based on the virtualization of collaborative learning with the aim of leveraging knowledge elicited during live sessions. During the CC–LR execution, the collaborative sessions are animated so learners can observe how avatars discuss and collaborate, how discussion threads grow and how knowledge is been constructed, refined and consolidated. In addition, complex aspects of the learning process can be incorporated in the CC–LRs during their creation, such as cognitive assessment and emotional awareness. The system produced from this research is tested to evaluate the CC‐LR enriched with complex information and analyze its effects in the discussion process. The research reported in this paper was undertaken within the Seventh Framework Programme (FP7) European project called 'Adaptive Learning via Intuitive/Interactive, Collaborative and Emotional systems'.